Single metal atom decorated photocatalysts : progress and challenges - Zeng, Lei (2021)
Photocatalysis has attracted intense attention due to its potential to solve the energy resource problem and environmental issues. The single metal atom decorated photocatalysts as a rising star become more and more popular because of the unique advantages of superior catalytic activities and ultrahigh atom utilization efficiency. The key function of single metal atom catalysts in photocatalytic reactions is boosting surface redox reactions by utilizing photogenerated charges, and has been verified by various spectroscopic and microscopic techniques. Nevertheless, the activities of the single metal atoms highly depend on the binding environment in the host photocatalyst that affect the adsorption and activation of reactants as well as the reaction energy barrier. Herein, this mini review summarizes recent progress on single metal atom decorated photocatalysts, and discusses the roles of the single metal atom catalysts in different types of host photocatalysts including organic, carbon-based and inorganic materials. The remaining challenges and future perspectives on the stability and activities of single atom catalysts in photocatalytic processes are elaborated in the end. We believe that this mini review will provide valuable overview on synthetic methods of different single atom photocatalysts for researchers towards future development of highly efficient photocatalysts.